Efek Pemberian Formula F-75 dan F-100 pada Anak Malnutrisi Penyerta Bronkopneumonia: Studi Kasus - khairunnisa, nuha; Prihatin, Setyo; Larasati, Meirina Dwi; Jaelani, Mohamad (NUTRITURE JOURNAL, 2026)
Background: Malnutrition among children under five remains a major public health problem in Indonesia. Severe malnutrition accompanied by pulmonary infections such as bronchopneumonia is still frequently encountered in healthcare facilities. These conditions interact in a vicious cycle in which infection increases energy requirements and worsens nutritional status, while malnutrition impairs immunity, aggravates disease severity, and increases mortality risk. Therefore, appropriate nutritional management is essential to support recovery and improve clinical outcomes. Objective: This case study aimed to describe the implementation of nutritional intervention using WHO therapeutic formulas (F-75 and F-100) to improve body weight in a child with malnutrition and bronchopneumonia. Methods: A case study was conducted on a pediatric patient diagnosed with malnutrition and bronchopneumonia. Energy and macronutrient requirements were calculated according to WHO recommendations. Nutritional intervention was provided through phased administration of WHO therapeutic formulas, starting with F-75 during stabilization and followed by F-100 during rehabilitation. Monitoring and evaluation included daily body weight measurements, documentation of formula intake, and dietary assessment using 24-hour recall and Comstock methods. Results: Administration of F-75 and F-100 improved nutritional status, resulting in a body weight gain of 7.2 g/kg/day, indicating an adequate response to treatment. Macronutrient intake also increased during hospitalization, reflecting improved nutritional adequacy. Conclusion: WHO therapeutic formulas F-75 and F-100 effectively improved body weight gain and macronutrient intake in a child with malnutrition and bronchopneumonia, supporting recovery during hospitalization.